منهج الإمام فخر الدين الرازي في توجيه القراءات من خلال تفسيره :‏ ‏سورتا الفاتحة والبقرة نموذجا /‏ - Abdul Hayyi bin Zulkifli (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2013)
This study examines the approach of Imam al-Fakhr al-Razi in explaining various recitations (taujih al-qiraat) models from his great work of interpretation of Qur'an (tafsir), Mafatih al-Ghayb, using surat al-Fatihah and al-Baqarah as examples. The aim of the study is also to describe the development of the knowledge of recitation ('ilm al-qiraat) and its explanation in different periods. To conduct this study, the inductive approach was used to analyse the book of Mafatih al-Ghayb, various books of 'ilm al-qiraat and their explanations, numerous books of tafsir, linguistics, biographies, and dictionaries by focusing on two surat, i.e. al-Fatihah and al-Baqarah. Another approach used was descriptive analytical. It was performed by reading and analysing related materials to learn more about al-Rāzi's approach. The study found that al-Razi was very concerned with various recitations (al-qiraat) in his interpretation of Qur'an. He was one of the scholars who used authentic recitation (alqiraat al-mutawatirah) and its explanation to determine the originality. Thus, al-Razi applied this method to the study of Al-Qur'an, tradition (al-atsar), Arabic linguistics, Arabic language and grammar, Arabic poetry, false recitation (al-qiraat as-syazzah), etc. Another result concluded that al-Razi's method of taujih al-qiraat referred to various other books of tafsir, al-qiraat, and languages, in which the rationalism approach was very much applied. In general, al-Razi had the same opinions about recitation and its explanation with other scholars of al-qurra (readers) and almufassirin (interpreters).